2020
DOI: 10.3390/biomedicines8090300
|View full text |Cite
|
Sign up to set email alerts
|

Bioabsorbable Osteofixation Materials for Maxillofacial Bone Surgery: A Review on Polymers and Magnesium-Based Materials

Abstract: Clinical application of osteofixation materials is essential in performing maxillofacial surgeries requiring rigid fixation of bone such as trauma surgery, orthognathic surgery, and skeletal reconstruction. In addition to the use of titanium plates and screws, clinical applications and attempts using bioabsorbable materials for osteofixation surgery are increasing with demands to avoid secondary surgery for the removal of plates and screws. Synthetic polymeric plates and screws were developed, reaching satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 131 publications
(165 reference statements)
0
47
0
2
Order By: Relevance
“…Except for the mandible, the flat bones of the maxillofacial region usually bear a lower load than long bones [ 18 ]. Researchers have found that Mg-based alloy fixation provides sufficient mechanical strength for maxillofacial bone healing [ 75 ]. In vitro pull-out experiments showed that pure Mg and AZ31 Mg alloy screws have similar fixation strengths to stainless steel screws [ 18 ].…”
Section: Mg-based Bms For Oral and Maxillofacial Applicationmentioning
confidence: 99%
“…Except for the mandible, the flat bones of the maxillofacial region usually bear a lower load than long bones [ 18 ]. Researchers have found that Mg-based alloy fixation provides sufficient mechanical strength for maxillofacial bone healing [ 75 ]. In vitro pull-out experiments showed that pure Mg and AZ31 Mg alloy screws have similar fixation strengths to stainless steel screws [ 18 ].…”
Section: Mg-based Bms For Oral and Maxillofacial Applicationmentioning
confidence: 99%
“…In recent years, magnesium alloys have been observed to have better mechanical properties than polymers used for osteosynthesis and still maintain the advantage of resorbability [ 31 , 32 ] and have also been used in bone regeneration for their biological proprieties [ 33 ]. However, it is known that the mechanical properties of magnesium implants are lower than those of medical titanium [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The role of the scaphoid within the structure and the mechanics of the carpus, including steering and rotation of the longitudinal axis of the scaphoid is an important kinematic component to consider in J o u r n a l P r e -p r o o f scaphoid fracture repair. Bioabsorbable devices have recently been investigated with renewed vigour in bony fixation 10 , with orthopaedic surgery having a long history of using absorbable metals intraoperatively with mixed results 11 . However, the advantages of bioabsorbable material use in scaphoid fracture fixation have not been evaluated in the literature.…”
Section: Introductionmentioning
confidence: 99%